Peran Keterikatan Kerja Dan Keterikatan Organisasional Terhadap Kinerja Karyawan - Rostiana, R, Siskawaty dan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to determine whether work engagement is divided into 3 dimensions namely vigor, dedication, and absorption and employee engagement which are divided into 7 dimensions, namely work environment, leadership, team and co-worker relations, training and career development, compensation, organizational policies, and workplace well-being has a role on employee performance which is divided into 5 dimensions, namely the quantity of work, quality of work, punctuality, attendance, and ability to cooperate. This research uses quantitative methods. The method of data collection uses a questionnaire distributed to 367 respondents who are employees of the Head Office at PT. XYZ with random sampling method. The analytical method used is multiple regression analysis using SPSS version 22.0. The results of the study show that the variables of work engagement and employee engagement have a role simultaneously or partially to the variable performance of employees with a 95% confidence level. Work engagement and employee engagement have a total contribution of 63% to employee performance. Among these two variables, the most important role in employee performance is work engagement. Additional analysis shows that there are effects of differences in age groups and length of work on employee performance and educational background not related to the good or not of employee performance.